P260 Point of Care Ultrasound (POCUS) when performed by gastroenterologists with 200 supervised scans is accurate and clinically useful for patients with Crohn's disease. (16th January 2018) - Wang, I; Kamm, M; Wong, D; Bell, S; Connell, W; Thompson, A; Novak, K; Wright, E
Abstract: Background: IBD imaging involves invasive ileo-colonoscopy, radiation-exposing CAT (Computerised Axial Tomography) or high cost and limited availability MRE (Magnetic Resonance Enterography). In contrast, point of care ultrasound (POCUS), performed by a gastroenterologist in the IBD clinic, provides immediate, cheap, and convenient imaging. Preliminary data suggest good accuracy, but confirmation is required. We hypothesised that POCUS provides accurate and clinically useful information in patients with Crohn's disease. Methods: Disease activity, disease extent and the presence of complications [entero-enteric fistula and extra mural complication (abscess)] were assessed by POCUS, MRE and ileo-colonoscopy. At a single-centre, a single-gastroenterologist conducted POCUS scans within three months of either MRE or ileo-colonoscopy without intervening change in medical therapy. The gastroenterologist had performed 200 previous supervised scans in patients with IBD at a high volume intestinal ultrasound centre (Foothills Medical Centre, Calgary, Canada), a training level regarded as the minimum required to achieve independent competence. The accuracy of POCUS was analysed with respect to both MRE and ileo-colonoscopy and its agreement with these modalities assessed using kappa coefficient. Results: 43 patients (49% males) with confirmed Crohn's disease had a POCUS that was paired with MRE and 38 patients (47% males) had a POCUS paired with ileo-colonoscopy. When compared with ileo-colonoscopy POCUS was accurate in the assessment of disease activity (sensitivity 72%, specificity 86%, ROC 0.79) and extent (sensitivity 85.7%, specificity 86%, ROC 0.86). No analysis was made for POCUS in relation to lleo-colonoscopy for the accuracy of diagnosing complications due to the low number of patients with complications diagnosed at ileo-colonoscopy. For POCUS and ileo-colonoscopy kappa estimates were 0.55 (95% CI 0.30–0.80) p < 0.001 for disease activity and 0.62 (95% CI 0.32 – 0.92) p < 0.001 for disease extent. When compared with MRE, POCUS was accurate in the assessment of disease activity (sensitivity 87.5%, specificity 61.1%, ROC 0.74), extent (sensitivity 77.8%, specificity 83.3%, ROC 0.81) and complications (sensitivity 85.7%, specificity 94.3%, ROC 0.90). Agreement between POCUS and MRE was good (kappa estimates 0.50 (95% CI 0.24–0.76) p < 0.001, 0.61 (95% CI 0.37–0.85) p < 0.001 and 0.76 (95% CI 0.50 – 1.00) p < 0.001) for disease activity, extent and complications respectively. Conclusions: POCUS performed by gastroenterologists with a minimum training fulfilment is accurate for assessing Crohn's disease activity, extent and the presence of complications.